Caspase-1 genetic variation is not associated with Alzheimer's disease risk - Berciano José; Valdivieso Fernando; Frank Ana; Martínez-García Ana; Pozueta Ana; Mateo Ignacio; Sánchez-Juan Pascual; Rodríguez-Rodríguez Eloy; Vázquez-Higuera José; Bullido María J; Combarros Onofre (BMC, 2010)
Abstract Background Interleukin (IL)-1β is a potent proinflammatory cytokine markedly overexpressed in the brains of patients with Alzheimer's disease (AD), and also involved in development of atherosclerosis and coronary artery disease. Caspase-1 (CASP1), formerly called IL-1β converting enzyme (ICE), mediates the cleavage of the inactive precursor of IL-1β into the biologically active form. CASP1 genetic variation (G+7/in6A, rs501192) has been associated with susceptibility to myocardial infarction and cardiovascular death risk. We examined the contribution of this gene to the susceptibility for AD. Methods We examined genetic variations of CASP1 by genotyping haplotype tagging SNPs (htSNPs) (rs501192, rs556205 and rs530537) in a group of 628 Spanish AD cases and 722 controls. Results There were no differences in the genotypic, allelic or haplotypic distributions between cases and controls in the overall analysis or after stratification by age, gender or APOE ε4 allele. Conclusion Our negative findings in the Spanish population argue against the hypothesis that CASP1 genetic variations are causally related to AD risk.